2014
DOI: 10.1177/0741932514533998
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Intervention to Enhance Reading Comprehension of Students With High-Functioning Autism Spectrum Disorder

Abstract: Students with high-functioning autism spectrum disorder (ASD) represent a rapidly growing segment of the population of school-age children with special needs (Centers for Disease Control and Prevention, 2012). By definition, these students do not meet the criteria for intellectual disability, and they could learn normally in a regular classroom environment. However, acquiring what is perhaps the most important learning skill, reading with comprehension, is a challenge for them (Frith & Snowling, 1983;Snowling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
1
31
1
5
Order By: Relevance
“…However, relevant reviews have identified a number of effective practices (Accardo, 2015;El Zein, Solis, Vaughn, & McCulley, 2014;Finnegan & Mazin, 2016). Identified effective practices include anaphoric cueing (Solis, McCulley, & Zein, 2013), compare and contrast diagrams (Carnahan & Williamson, 2013), cooperative learning (Kamps, Barbetta, Leonard, & Delquadri, 1994;Kamps, Leonard, Potucek, & Garrison-Harrell, 1995;Whalon & Hanline, 2008), direct/explicit instruction (Flores & Ganz, 2007;Flores & Ganz, 2009;Roux, Dion, Barrette, Dupere, & Fuchs, 2014), graphic organizers (Carnahan & Williamson, 2013), question generation (Hua et al, 2012), read-alouds (Mims, Hudson, & Browder, 2012), reciprocal questioning (Whalon & Hanline, 2008), story structure maps/character event maps (Stringfield, Luscre, & Gast, 2011;Williamson, Carnahan, Birri, & Swoboda, 2014), and systematic prompts (Mims et al, 2012). Of the instructional practices, only systematic prompts and visual supports, for example, graphic organizers and diagrams, have been identified as evidence based (Knight & Sartini, 2015).…”
mentioning
confidence: 99%
“…However, relevant reviews have identified a number of effective practices (Accardo, 2015;El Zein, Solis, Vaughn, & McCulley, 2014;Finnegan & Mazin, 2016). Identified effective practices include anaphoric cueing (Solis, McCulley, & Zein, 2013), compare and contrast diagrams (Carnahan & Williamson, 2013), cooperative learning (Kamps, Barbetta, Leonard, & Delquadri, 1994;Kamps, Leonard, Potucek, & Garrison-Harrell, 1995;Whalon & Hanline, 2008), direct/explicit instruction (Flores & Ganz, 2007;Flores & Ganz, 2009;Roux, Dion, Barrette, Dupere, & Fuchs, 2014), graphic organizers (Carnahan & Williamson, 2013), question generation (Hua et al, 2012), read-alouds (Mims, Hudson, & Browder, 2012), reciprocal questioning (Whalon & Hanline, 2008), story structure maps/character event maps (Stringfield, Luscre, & Gast, 2011;Williamson, Carnahan, Birri, & Swoboda, 2014), and systematic prompts (Mims et al, 2012). Of the instructional practices, only systematic prompts and visual supports, for example, graphic organizers and diagrams, have been identified as evidence based (Knight & Sartini, 2015).…”
mentioning
confidence: 99%
“…Many features of the interventions of these three recent investigations (Carnahan & Williamson, 2013;Williamson et al, 2015) align with findings of groupdesign intervention studies of students with ASD (O'Connor & Klein, 2004;Roux et al, 2015).…”
Section: Reading Intervention For Adolescents With Asdmentioning
confidence: 61%
“…Common across all of the intervention studies is the instructional practices of modeling of cognitive processes, discussion of key concepts, and guided and independent practice (El Zein et al, 2014). This small yet growing body of literature supports the notion that students with ASD who have difficulty understanding expository text benefit from interventions that include visual supports, vocabulary instruction, main idea summarization strategies, discussion, and questioning (Asberg & Sandberg, 2010;Carnahan & Williamson, 2013;El Zein, Solis, & Lang, 2016;Flores & Ganz, 2007;Ganz & Flores, 2009;Knight, 2010;Roux et al, 2015;Solis et al, 2015;Stringfield et al, 2011;Van Riper, 2010;Whalon & Hanline, 2008).…”
Section: Reading Intervention For Adolescents With Asdmentioning
confidence: 94%
“…Por el contrario, otros estudios señalan que, en primer lugar, el aprendizaje es más efectivo cuando se realiza de forma individual y mediante programas de instrucciones directas, es decir, el término conocido en inglés como Direct Instruction (DI), ya que mejoran e implementan su comprensión. Para después pasar a combinar con el trabajo en grupos cooperativos con sus iguales en un aula ordinaria, de esta forma aprenderán estrategias para las relaciones sociales (Flores y Ganz, 2007;Flores, Nelson, Hinton, Franklin, T., Strozier, Terry, Franklin, 2013;Roux, Dion, Barrette, Dupéré y Fuchs, 2015;Shillingsburg, Bowen, Peterman y Gayman, 2015;Braun, Austin y Ledbetter-Cho, 2017;Head, Flores y Shippen, 2018).…”
Section: Resultsunclassified
“…En contraposición en otros estudios se obtienen mejores resultados si el alumnado con TEA de nivel 1 no está incluido en su aula ordinaria durante el aprendizaje de la lectura. Además, en otros estudios se presentan mejores resultados cuando al inicio del proceso de enseñanza-aprendizaje de la lectura el/la alumno/a no se encuentra incluido en su aula ordinaria y a medida que progresa en este aprendizaje se incluye en grupos cooperativos de su aula de referencia (Kamps et al, 1994;Flores y Ganz, 2007;Ledford et al, 2008;Whalon et al, 2008;LaBarbera y Soto-Hinman, 2009;Flores et al, 2013;Roux et al, 2015;Shillingsburg et al, 2015;Braun et al, 2017;Head et al, 2018;Kim et al,2018).…”
Section: Discusión Y Conclusionesunclassified